2017
DOI: 10.1177/2325967117736726
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Most Important Factors Involved in Ranking Orthopaedic Sports Medicine Fellowship Applicants

Abstract: Background:Orthopaedic surgery residencies and certain fellowships are becoming increasingly competitive. Several studies have identified important factors to be taken into account when selecting medical students for residency interviews. Similar information for selecting orthopaedic sports medicine fellows does not exist.Purpose:To determine the most important factors that orthopaedic sports medicine fellowship program directors (PDs) take into account when ranking applicants.Study Design:Cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 21 publications
(53 reference statements)
3
50
0
Order By: Relevance
“…In a study surveying orthopedic fellowship program directors in the U.S. the most important criteria in deciding to offer an interview were letters of recommendation from subspecialty faculty, quality of residency program and letter from the program director. 7 In line with the findings of our study advanced degree, extracurricular activities and quality of medical school were less important. Similar to our findings ophthalmic plastic and reconstructive surgery and pediatric emergency medicine program directors highly valued interview performance, ability to work/communicate with others and letters of recommendation from subspecialty faculty when ranking a fellow.…”
Section: Discussionsupporting
confidence: 89%
“…In a study surveying orthopedic fellowship program directors in the U.S. the most important criteria in deciding to offer an interview were letters of recommendation from subspecialty faculty, quality of residency program and letter from the program director. 7 In line with the findings of our study advanced degree, extracurricular activities and quality of medical school were less important. Similar to our findings ophthalmic plastic and reconstructive surgery and pediatric emergency medicine program directors highly valued interview performance, ability to work/communicate with others and letters of recommendation from subspecialty faculty when ranking a fellow.…”
Section: Discussionsupporting
confidence: 89%
“…Published studies on orthopaedic education commonly have response rates that are similar to ours. 1 , 6 , 9 Our survey may not have included all factors that fellowship directors and/or applicants consider to be important in the application, selection, interview, and ranking process. Another potential factor that PDs could take into account would be the evaluation of performance on a manual skills test.…”
Section: Discussionmentioning
confidence: 99%
“…The school should create additional opportunities for these student champions to stay involved in the development, and eventual rollout, of the XR product throughout their education. For example, in exchange for their continued participation, the school could choose to grant elective credit or research opportunities, which have been shown to be associated with high match rates in a student’s specialty of choice [15]. We believe that medical students are more likely to engage with the XR tool, and use it throughout the continuum of their medical education, if they believe it is an investment in their future as a physician.…”
Section: Student-centered Iterationmentioning
confidence: 99%